Wpływ Prędkości Odkształcania na Krzywa Umocnienia dla Aluminium - Klepaczko, J. (Engineering Transactions, 1964)
The paper presents experimental results obtained with aluminium tube test pieces subject to torsion at fixe different rates ranging from tgy = 1,66-10-5 1/sec to tgy = 0,624 1/sec. The tests have been performed by means of a special machine constructed at the Plasticity Group of the IPPT.As a result of experiments the influence of strain-rate on the strain-hardening curve has been found to be nonexisting in a certain velocity range. Empirical relations have been obtained describing this phenomenon. The paper contains also a brief discussion of the results obtained from the viewpoint of tests by other authors and that of physics of metals.